Hierarchical Self‐Assembly of Supramolecular Coordination Polymers Using Giant Metal–Organic Nanocapsules as Building Blocks. Issue 54 (12th September 2018) - Zhang, Chen; Wang, Fang; Patil, Rahul S.; Barnes, Charles L.; Li, Tao; Atwood, Jerry L.
Abstract: Controlling the self‐assembly of giant molecular building blocks into complex architectures with similar hierarchy to biological species remains a major challenge in supramolecular chemistry. Akin to protein structure, here we present the self‐assembly of giant molecular nanocapsules into supramolecular coordination polymers with controlled hierarchy from primary to secondary and tertiary structures. First, we successfully prepared discrete nanocapsules (secondary structures) consisting of multicomponents, such as organic macrocycles and metal‐based secondary building units (primary structures). Second, these nanocapsules can self‐organize into various 2D and 3D supramolecular coordination polymers (tertiary structures) through coordination‐driven assembly. The periphery 24 flexible alkyl chains and 24 metal ions available for potential coordination make these nanocapsules comparable to functionalized solid nanoparticles with non‐specific binding sites at the surface and allow the nanocapsules to self‐adjust their orientations and coordination modes to facilitate the self‐assembly process. This study sheds light on the self‐assembly of giant building units with complex molecular structures and opens up possibilities for the design of new hierarchical architectures with innovative properties and functions in many applications such as biomimics, biomedicine, and molecular devices. Abstract : Big friendly giant chemistry ! Hierarchical self‐assembly using giant metal–organic nanocapsules as building blocks is presented here. The resulting supramolecular coordination polymers possess primary, secondary, and tertiary structures, akin to complex protein structures.